A case of mesenteric gastro intestinal stromal tumors: a diagnostic dilemma - R., Rajalakshmi; V., Rajakumar (International Surgery Journal, 2022)
Gastro intestinal stromal tumors (GIST) are non-epithelial tumors of gastrointestinal tract (GIT) arising from mesenchymal cells and interstitial cells of Cajal. It accounts for <1% of all of gastro-intestinal (GI) tumors and <5% of all GI malignancies. GIST most commonly involves stomach and small intestine, but rarely involves mesentery. Surgical resection is the main stay of treatment. Post-operative use of imatinib, delays the recurrence and improves the survival rate. In our study, we report a case of mesenteric GIST, a very rare entity and discuss the course of clinical presentation, diagnosis, management and prognosis.